CZYNNIKI ROZWOJU PROJECT FINANCE W POLSCE - Świątek, Jakub (Wydział Prawa i Administracji UAM, 2002)
In the view of the economic conditions and infrastructural needs of the Polish economy project finance as an investment strategy should certainly gain in popularity in the coming years in Poland. What makes this method especially desirable is above all insufficient investment capital in Polish companies. Additionally, this deficit deprives companies of possible support from the State. Project finance gives real benefits to project sponsors, who have an opportunity to make investments outside their own companies. Because whole businesses are founded from scratch in the process, such investments create jobs at a number of stages. Beside businesses and the State Treasury, also banks can benefit as lenders from project finance by earning profits from loan interests. The political stability of Poland, engagement of international banks in the market and twenty years of experience gained by institutions financing project finance all reduce the risks involved in the project to a level that is considered acceptable by banks in Poland. However, promoting project finance investments is impossible without some structural reforms of the Polish economy and legal system. Above all, it is necessary to further privatise those sectors which for years have seen a development of project finance in the world: in the transport, power, and extractive industries. Stability of the law and reduced red tape also condition a boost of project finance investments. It is also necessary to popularize this type of investments among potential sponsors, especially private businesses and local governments, training their staff in project finance.
DEVELOPMENT FACTORS OF PROJECT FINANCE IN POLAND